Supplier selection process using ELECTRE method - Bi̇rgün, Semra; Ci̇han, Emrah (2010 IEEE International Conference on Intelligent Systems and Knowledge Engineering, 2010)
In today's competitive environment, effective supplier selection process is very important for the success of manufacturing organizations. In this context, supplier selection represents one of the most important functions to be performed by the purchasing departments. Supplier selection is a multi-criteria problem including many factors (criteria). In the literature, a number of models and techniques have been developed to deal with selecting and evaluating suppliers. In this paper, ELECTRE, which is one of these methods, is discussed with a case study illustration.